2004
DOI: 10.1038/sj.onc.1208306
|View full text |Cite
|
Sign up to set email alerts
|

Definition and characterization of a region of 1p36.3 consistently deleted in neuroblastoma

Abstract: Substantial genomic and functional evidence from primary tumors and cell lines indicates that a consistent region of distal chromosome 1p is deleted in a sizable proportion of human neuroblastomas, suggesting that this region contains one or more tumor suppressor genes. To determine systematically and precisely the location and extent of 1p deletion in neuroblastomas, we performed allelic loss studies of 737 primary neuroblastomas and genotype analysis of 46 neuroblastoma cell lines. Together, the results defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
129
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(142 citation statements)
references
References 57 publications
8
129
1
4
Order By: Relevance
“…Whereas breakpoints are widely dispersed along chromosome arms 1p, 2p, 3p and 17q, they lie closer together on chromosome 11q, at 11q23, in accordance with published data (Schleiermacher et al, 2004;Stallings et al, 2004;White et al, 2005;Spitz et al, 2006). Further studies using FISH or high-resolution CGH will be needed to map the breakpoints precisely.…”
Section: Discussionsupporting
confidence: 84%
“…Whereas breakpoints are widely dispersed along chromosome arms 1p, 2p, 3p and 17q, they lie closer together on chromosome 11q, at 11q23, in accordance with published data (Schleiermacher et al, 2004;Stallings et al, 2004;White et al, 2005;Spitz et al, 2006). Further studies using FISH or high-resolution CGH will be needed to map the breakpoints precisely.…”
Section: Discussionsupporting
confidence: 84%
“…By contrast, we did find that in rare cases of pancreatic cancer, EphA2 protein overexpression may specifically result from amplification of 1p36.12. Chromosomal alterations involving 1p have been reported in a variety of human cancer types, including pancreatic carcinoma [32,33], with most studies implicating the presence of a tumor suppressor gene(s) on this chromosome arm [34,35]. However, the lack of inactivating mutations of EPHA2 reported in this study indicates that EPHA2 functions in a manner unlike that of the other Eph receptor family members targeted by inactivating mutations.…”
Section: Discussioncontrasting
confidence: 51%
“…CASZ1 (1p36.22) localizes to one of the commonly deleted region in NB on chr1p between the markers D1S508 and D1S244. 3 Although the recent study in 184 primary NB with 1p LOH showed that 1p36.3 (minimally between D1S2795 and D1S252) is the shortest region of overlap (SRO), 24 we found in their study that loss of CASZ1 occurs in 180 of the 184 (98%) 1p LOH primary NB tumors. In this study, we provide functional evidence that CASZ1 is a tumor-suppressor gene.…”
Section: Resultsmentioning
confidence: 86%